Imported pottery in Central Illyricum – a case study: Caričin grad (Iustiniana Prima) - Bikić, Vesna; Ivanišević, Vujadin (Rei Cretariae Romanae Fautorum Acta, 2012)
The region of Central Illyricum regained importance when the limes on the Danube was renewed in the time of Anastasius I after the treaty signed in 510 AD between Byzantium and the Ostrogoths. Beside the reconstruction of the fortifications, the arrival of the army certainly contributed to reviving the stagnant economy and to increasing trade and traffic along the main Balkan communication routes after the destruction by the Huns in 441 and 443. Despite all efforts, the renewal of the cities was limited only to a part of the former urban cores, testifying to the significant reduction of the city population in the 6th century – in comparison to the 4th century and the period of the Illyrian provinces’ expansion. The large private estates and villae publicae erected in the plains and large valleys, which had been damaged in the barbarian raids at the end of the 4th and 5th centuries, did not retrieve their former role. For example, the warehouses for agricultural products, and the wine-pools of the 4th century in the important villa publica in Mediana, were not renewed in the 6th century. An important role in the economic recovery was apparently played by the rural population that inhabited the broader region of this, one should stress, poorly urbanised region of the Empire. The northern part of the territory was the only urbanised region, with its cities on the Danube and the Sava rivers. In the interior of this vast region, we encounter the rare urban centres as Naissus and Ulpiana, erected on important Balkan crossroads, and Municipium Dardanorum on the River Ibar, near the Dardanian mines and Municipium S in the Lim river valley. On the other hand, the whole of this region, particularly its central area, was intersected by a network of large and small fortifications, the majority of which were refugia.